2020
DOI: 10.18549/pharmpract.2020.4.2171
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists’ evolving role in Canadian primary health care: a vision of harmonization in a patchwork system

Abstract: Canada’s universal public health care system provides physician, diagnostic, and hospital services at no cost to all Canadians, accounting for approximately 70% of the 264 billion CAD spent in health expenditure yearly. Pharmacy-related services, including prescription drugs, however, are not universally publicly insured. Although this system underpins the Canadian identity, primary health care reform has long been desired by Canadians wanting better access to high quality, effective, patient-centred, and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…This study demonstrates the potential roles community pharmacy staff can have in raising public awareness of RA, the early identi cation of RA, early symptom management and signposting towards prompt and de nitive treatment initiation. This aligns with current policy in many countries, including the UK, to expand pharmacy services (33)(34)(35)(36) and to facilitate integration within primary care (37,38). With the correct knowledge and training, pharmacy staff are well positioned to use their clinical skills to identify and refer patients to their GPs where appropriate.…”
Section: Discussionsupporting
confidence: 70%
“…This study demonstrates the potential roles community pharmacy staff can have in raising public awareness of RA, the early identi cation of RA, early symptom management and signposting towards prompt and de nitive treatment initiation. This aligns with current policy in many countries, including the UK, to expand pharmacy services (33)(34)(35)(36) and to facilitate integration within primary care (37,38). With the correct knowledge and training, pharmacy staff are well positioned to use their clinical skills to identify and refer patients to their GPs where appropriate.…”
Section: Discussionsupporting
confidence: 70%
“…Pharmacists are highly accessible and trusted professionals with expertise in medication management [9]. Community pharmacists see their patients face-to-face regularly, which provides opportunities for building relationships and communicating directly with patients [10]. A recent study in Canada reported that approximately 55% of Canadians visit their community pharmacy at least once weekly [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, the movement to include pharmacists as essential members of PCTs has gained traction in a number of countries, including Canada [ 9 , 11 , 12 ], the United States [ 13 , 14 , 15 ], the United Kingdom [ 16 , 17 ], Australia [ 18 ], Malaysia [ 19 , 20 , 21 ], and Brazil [ 22 ]. Pharmacists integrated into interdisciplinary PCTs globally demonstrated their significant role in many direct patient care activities, including medication management, identifying adverse or incorrect medication usage, counselling on medications, and effectively optimizing a patient’s understanding of their own medication regimens to enhance overall quality of life [ 9 , 23 ].…”
Section: Introductionmentioning
confidence: 99%